2019
DOI: 10.1186/s12302-019-0207-z
|View full text |Cite|
|
Sign up to set email alerts
|

Spatiotemporal variation and source apportionment of organotin compounds in sediments in the Yangtze Estuary

Abstract: Background: The Yangtze Estuary is a vital habitat and breeding ground for many rare species (e.g., Chinese sturgeon, Chinese paddlefish). From the view of marine ecosystem health, organotin compounds (OTCs) should be of great concern in this area based on their broad applications and potential threats. At present study, five OTC species were determined in 28 and 26 surface sediments from the Yangtze Estuary (including the Nearshore area, Estuarine Turbidity Maxima (ETM) zone and Plume zone) in 2015 and 2016, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Besides leaching artificial additives (i.e., plasticizers, colorants, and flame retardants), MPs can also leach absorbed organic compounds into the environment. After irradiation with UV and visible light, Chen et al ( 2019) detected the release of organotin compounds (OTCs) from PVC microplastics (MPs) [86]. Four types of OTC, namely dimethyltin (DMT), monomethyltin (MMT), dibutyltin (DBT), and monobutyltin (MBT), were observed to be released from PVC in the dark.…”
Section: Release Of Dissolved Organic Compounds From Microplasticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides leaching artificial additives (i.e., plasticizers, colorants, and flame retardants), MPs can also leach absorbed organic compounds into the environment. After irradiation with UV and visible light, Chen et al ( 2019) detected the release of organotin compounds (OTCs) from PVC microplastics (MPs) [86]. Four types of OTC, namely dimethyltin (DMT), monomethyltin (MMT), dibutyltin (DBT), and monobutyltin (MBT), were observed to be released from PVC in the dark.…”
Section: Release Of Dissolved Organic Compounds From Microplasticsmentioning
confidence: 99%
“…The reason for this is that changes in salinity can alter the water and compound chemistry, affecting the pH, ionic strength, polarity, and other parameters [19]. found that the release of organotin compounds from PVC particles was inhibited under high-salinity conditions, probably due to organotin's re-adsorption on PVC [86].…”
Section: Effects Of Environmental Factorsmentioning
confidence: 99%
“…In costal systems, sedimentary concentration levels of TBT were reported as ranging from 9 to 469 ng/g dw from Jinhae Bay in Korea [8], and from 0.3 to 174.7 ng/g dw at the ports of Xiamen, Shantou and Huiyang in China [9]. Chen et al [10] found that sediment samples from the Estuarine Turbidity Maxima zone of the Yangtze Estuary had the TBT levels above 10 ng/g dw, which are sufficient to bring harmful effects to benthic organisms and pose serious ecological risks. The organotin compounds' contamination was demonstrated to vary slightly during the year 2014-2016 in the Yangtze Estuary [10].…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al [10] found that sediment samples from the Estuarine Turbidity Maxima zone of the Yangtze Estuary had the TBT levels above 10 ng/g dw, which are sufficient to bring harmful effects to benthic organisms and pose serious ecological risks. The organotin compounds' contamination was demonstrated to vary slightly during the year 2014-2016 in the Yangtze Estuary [10]. It is expected that the TBT and TPT effects will be present in marine environments and freshwater ecosystems for some years ahead [11].…”
Section: Introductionmentioning
confidence: 99%